Tony Lawson on money - Menšík Josef (Review of Economic Perspectives, 2023)
Tony Lawson, the leading figure of the Cambridge Social Ontology Group, recently published a series of papers devoted to the question of the nature of money. These contributions have to be understood in the context of his broader approach to social ontology, the so called social positioning theory. While at first glance Lawson’s monetary ideas might appear disconnected and sometimes even contradictory or mistaken, there is a consistent vision behind them which is Lawson general social ontology. Lawson’s elaboration of the nature of money is not the only one compatible with the social positioning theory and an alternative one is briefly proposed in the paper. While systematising various Lawson’s monetary contributions, attention has been paid to several particular discrepancies and mistakes and their rectification. At the end of the paper, some lessons from analysing Lawson’s monetary contributions are drawn for his general approach to social ontology.